THE CHANGES OF RATIO OF SERRATUS ANTERIOR TO UPPER TRAPEZIUS AND PECTORALIS MAJOR ACCORDING TO SURFACE TILT ANGLE WITH AND WITHOUT WINGING SCAPULAE - Gu, Qian; Kim, Tae-Ho; Hyun, Sang-Wook (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study was to examine differences in a ratio of serratus anterior to upper trapezius and a ratio of serratus anterior to pectoralis major according to surface tilt angle during push-up plus exercise with and without winging scapulae. Thirty-two subjects participated in this experiment. The subjects were divided into 2 groups: winging scapular group and normal subject group. Surface EMG was used to measure muscle activity of serratus anterior, the upper trapezius and the pectoralis major. The values of a ratio of serratus anterior to upper trapezius is %MVIC of serratus anterior divided by %MVIC of upper trapezius. All subjects performed push-up plus exercises on a surface at four different tilt angles (0°, 30°, 60°, and 90° tilt angle). There were significant difference in the ratio of serratus anterior to upper trapezius and the ratio of serratus anterior to pectoralis major across the four surfaces in winging scapular group (p＜.05). There were significant difference in the ratio of serratus anterior to upper trapezius on 90˚, 60˚, and 30˚ surface angle between two groups (p＜.05). There were significant difference in the ratio of serratus anterior to pectoralis major on 30˚ and 0˚ surface angle between two groups (p＜.05). This study suggest that performance of push-up plus exercise on the 30˚ and at a 0˚ tilt angle ground can be regarded as the best choice to strengthen the serratus anterior muscles with winging scapulae, and it is most effective for healthy adults to exercise at a 0˚ tilt angle ground.